2016
DOI: 10.1177/1478210316679069
|View full text |Cite
|
Sign up to set email alerts
|

Reforms in the policy of English language teaching in Malaysia

Abstract: This paper reviews reforms related to English language teaching in the Malaysian education system. It begins by tracing the history of Malaysia as a former British colony which has had significant influences on the status of English in the country. Then, it reviews the key educational reforms which have mainly centred on language policy, thus putting pressure on teachers who are at the front-line for the implementation of the new reforms. This is followed by the discussion on the changing approaches in the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(72 citation statements)
references
References 23 publications
2
70
0
Order By: Relevance
“…Nishimuro and Borg (2013) claim that teacher cognition is formed by thoughts, knowledge and beliefs and has an impact on instructional decisions. Professional knowledge is primarily gained at teacher training institutions and this knowledge affects the thoughts (Rashid, Rahman, & Rahman, 2016;Rashid, Rahman, & Yunus, 2017). The practice, on the other hand, displays the beliefs.…”
Section: Sources Of the Held Beliefsmentioning
confidence: 99%
“…Nishimuro and Borg (2013) claim that teacher cognition is formed by thoughts, knowledge and beliefs and has an impact on instructional decisions. Professional knowledge is primarily gained at teacher training institutions and this knowledge affects the thoughts (Rashid, Rahman, & Rahman, 2016;Rashid, Rahman, & Yunus, 2017). The practice, on the other hand, displays the beliefs.…”
Section: Sources Of the Held Beliefsmentioning
confidence: 99%
“…Furthermore, expensive state-of-the-art CDs were produced alongside printed materials, requiring the use of laptops, LCDs and installation of special screens in the classrooms, most of which was foreign to the teachers. Nonetheless, this initiative failed mainly because it was not well planned and its implementation was made in haste (Rashid et al, 2017). Research conducted post PPSMI implementation revealed that only 4% of Mathematics and Science teachers used 90% or more of English in the teaching and learning of the two subjects, and that students who had poor command of English could not acquire the knowledge of Mathematics and Science as they were not proficient (Yang & Ishak, 2012).…”
Section: English In Malaysia: a Case Of Schism Between Planning And Imentioning
confidence: 99%
“…Malaysia has to make sure that teachers develop the right teaching skills to teach English more effectively (Rashid, Abdul Rahman, & Yunus, 2016 Learning a second language is a complex process and research has only given partial answers to policy questions. There is no 'one-size fits all' solution that can be recommended to teachers and school systems to improve English learning outcomes.…”
Section: Improving Teachers' Capacity To Teach Englishmentioning
confidence: 99%